2017
DOI: 10.1088/1755-1315/78/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Meteorological Factors on PM2.5 Variations in Hong Kong

Abstract: Abstract. This paper aims to explore the impact of meteorological factors on PM2.5 concentrations in Hong Kong. The PM2.5 and meteorology data including temperature, pressure, rainfall, relative humidity (RH), wind speed and wind direction from January to December of 2013 were collected. The correlation analysis between PM2.5 and meteorological factors were conducted for each month and season. The meteorology data were classified into several intervals and the mean PM2.5 concentrations for each interval were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 8 publications
(10 reference statements)
5
33
1
1
Order By: Relevance
“…Relative humidity showed a significant (p value < .001) negative correlation with particulate matter (PM 2.5 and PM 10 ) in all seasons (Figure 7, Figure S3, and Figure S4). This result is very consistent with previous studies that showed that high relative humidity (>70%) played a significant role in reducing particulate matter concentration (Li, Feng, and Liang 2017;Lou et al 2017). The hygroscopic nature of particles could be another reason for negative correlation of coarse particles with relative humidity (RH) in all seasons.…”
Section: Effect Of the Monsoon Season On Pollutant Concentrationsupporting
confidence: 92%
“…Relative humidity showed a significant (p value < .001) negative correlation with particulate matter (PM 2.5 and PM 10 ) in all seasons (Figure 7, Figure S3, and Figure S4). This result is very consistent with previous studies that showed that high relative humidity (>70%) played a significant role in reducing particulate matter concentration (Li, Feng, and Liang 2017;Lou et al 2017). The hygroscopic nature of particles could be another reason for negative correlation of coarse particles with relative humidity (RH) in all seasons.…”
Section: Effect Of the Monsoon Season On Pollutant Concentrationsupporting
confidence: 92%
“…PM concentration in wet season is lower due to higher wind speed as compared with dry season which had lower wind speed as shown in Table 2. This is in agreement with the finding of other researcher, which showed that low wind speed increases PM level while increase in wind speed lowers PM concentration through wind dispersion and dry deposition [23,26].…”
Section: Wind Speedsupporting
confidence: 94%
“…The wet season PM loading is contributed mostly by the SW, W, NW and S winds than any other wind direction while the dry season particulate matter contribution at Woji was dominated by the N, NW and NE wind direction. The result therefore confirms that wind direction influences particulate matter concentration at Woji, which is in agreement with the findings of these researchers [23,30].…”
Section: Relative Humiditysupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, wind speed has different impacts on fine and coarse particles. It was shown that the fine PM concentrations decreased gradually with the increase of wind speed, while coarse PM concentrations would increase due to dust resuspension under strong winds (X. Li, Feng, et al, ; B. Zhang, Jiao, et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%